CDKN1B (p27/kip1) enhances drug-tolerant persister CTCs by restricting polyploidy following mitotic inhibitors - Elad Horwitz; Taronish D. Dubash; Annamaria Szabolcs; Ben S. Wittner; Johannes Kreuzer; Robert Morris; Aditya Bardia; Brian Chirn; Devon Wiley; Dante Che; Hunter C. Russell; Xcanda Ixchel Herrera Lopez; et al. (Proceedings of the National Academy of Sciences, 2025)
The mitotic inhibitor docetaxel (DTX) is often used to treat endocrine-refractory metastatic breast cancer, but initial responses are mitigated as patients develop disease progression. Using a cohort of ex vivo cultured circulating tumor cells (CTCs) from patients with heavily pretreated breast cancer (n=18), we find distinct patterns of response to DTX, which are intrinsic and independent of past clinical treatment with taxanes. In some CTC cultures, treatment with a single dose of DTX results in complete cell killing, associated with accumulation of nonviable polyploid (≥8 N) cells arising from endomitosis. In other CTC cultures, a transient viable drug-tolerant persister (DTP) population emerges, ultimately enabling renewed proliferation of CTCs with preserved parental cell ploidy and restored DTX sensitivity identical to that of the pretreated culture. In these CTCs, efficient cell cycle exit generates a ≤4 N drug-tolerant state dependent on CDKN1B (p27/kip1). Exposure to DTX triggers stabilization of CDKN1B through AKT-mediated phosphorylation at serine 10. Suppression of CDKN1B reduces the number of persister CTCs, increases ≥8 N mitotic cells and abrogates regrowth after DTX exposure. Thus, CDKN1B-mediated suppression of endomitosis contributes to the initiation of a reversible drug-tolerant persister state following mitotic inhibitors in advanced patient-derived breast cancer cells.